Jewish Theology about the other Nations and its Impacts on the Humanity - Dr. Muhammad Sajjad Malik,; Dr. Sadna Zeb,; Dr. Farhad Ullah,; Miss Shabnam Fazal,; Miss Enaya Tariq, (Al-Qanṭara, 2022)
Abstract: In this Paper, it has been endeavored to employee the misinterpreted and so-called slogan and claim by Jews to investigates the reality of the human history facts and its impacts on the humanity. Jews refer to the followers of Judaism who are descendants of the ancient Israelites. The total number of Jews worldwide cannot be fully estimated, but their number is between 12 and 14 million, the majority of whom reside in the United States and Israel. The belief of Jews and Christians regarding the hereafter is that there will be a resurrection and there will be punishment and punishment, but each of them considers himself worthy of paradise and considers the other as lost. The related belief has been explicitly mentioned by Allah in the Holy Qur'an and refuted by saying that these are their own thoughts and that these people are pinning their hopes on Allah which has nothing to do with reality, and He said: He who purifies his religion for the sake of Allah will go to Paradise Key Words: Judaism, Islam, Christianity, Society, Humanity, History